Digital Narratives and Tradition: The Role of NU Kids Animations in Early Islamic Education - Rashid Said Al Mushaiqri, Mahfouda; Sulistio, Dody (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – This study aims to analyze the impact of animated content on the NU Kids YouTube channel on traditional Islamic education for early childhood by examining viewership metrics, community engagement, behavioral changes in children, and how these animations integrate character education, appreciation for local traditions, and the formation of a moderate religious identity. Design/methods/approach – A netnographic approach was employed to observe and analyze 7 out of 13 available videos on the NU Kids Sumenep channel. These 7 videos were selected based on their thematic relevance to the research objectives, focusing on the portrayal of Nahdlatul Ulama’s history, character education, and the development of religious identity. Thematic analysis was used to identify key themes in these videos, including representations of Nahdlatul Ulama history, character education, and the development of religious identity. Findings – The findings indicate that NU Kids animations successfully promote traditional Islamic values rooted in local traditions. For instance, episodes such as "The Founding of Nahdlatul Ulama" and "The Story of Kiai Hasyim Asy'ari" emphasize respect for elders, community solidarity, and the integration of Islamic principles with local customs, which resonate deeply with audiences. The channel effectively builds a strong digital community and strengthens the collective identity of the NU community in the era of globalization. Research implications/limitations – The study is limited to the community analyzed, which may be confined to those already affiliated with Nahdlatul Ulama. The research primarily relies on public data such as view counts and comments, which may not fully reflect long-term impacts. Practical implications – This study demonstrates that digital media, such as YouTube, can be an effective tool for disseminating traditional Islamic teachings to young audiences. The findings could influence the development of educational content based on local values in the future. Originality/value – This research provides new insights into the role of digital media in traditional Islamic education, particularly in early childhood education, by demonstrating how platforms like NU Kids integrate local cultural narratives with religious teachings, employ storytelling and digital tools to foster collective identity, preserve traditional values, and shape the younger generation's identity in a rapidly globalizing world. Paper type Research paper